How can those engaging in chemsex best be supported? An online survey to gain intelligence in Greater Manchester. (February 2018) - Tomkins, Andrew; Vivancos, Roberto; Ward, Chris; Kliner, Merav
Reports of sexualised drug taking (chemsex) have increased significantly in recent years. There is currently limited intelligence on chemsex outside of London. An anonymous survey was promoted via several sources including voluntary services and a sexual health clinic in order to establish the risks associated with chemsex, and how support services can best be tailored to meet the needs of those in Greater Manchester, UK. Quantitative and qualitative data were collected on demographics, drug use, sexual practices and barriers and facilitators to accessing support. Fifty-two men who have sex with men completed the online survey. Thirty-nine (75%) were HIV-positive and 11 (21%) were hepatitis C virus (HCV) positive, all of whom were HIV/HCV co-infected. The most commonly used drugs were mephedrone (81%) and gamma hydroxybutyrate/gamma butyrolactone (79%). Nineteen (37%) reported ever injecting drugs. High-risk sexual practices were reported by respondents. Barriers to accessing support included a fear of being recognised. Findings demonstrate those engaging in chemsex are participating in a number of high-risk sexual practices, taking substances with significant risks and administering these substances in potentially high-risk ways. Results demonstrate the need for promotion of existing services, with key areas to target where chemsex sessions are most commonly arranged. Results may be useful in other metropolitan cities, both for commissioning and tailoring of chemsex support services.